Impact of abnormal cerebrovascular reactivity on BOLD fMRI: a preliminary investigation of moyamoya disease. (30th August 2016) - Mazerolle, Erin L.; Ma, Yuhan; Sinclair, David; Pike, G. Bruce
Summary: Blood oxygen level‐dependent (BOLD) functional magnetic resonance imaging (fMRI) studies of patients with cerebrovascular disease have largely ignored the confounds associated with abnormal cerebral blood flow, vascular reactivity and neurovascular coupling. We studied BOLD fMRI activation and cerebrovascular reactivity in moyamoya disease. To characterize the impact of remote vascular demands on BOLD fMRI measurements, we varied the vascular territories engaged by manipulating the experimental task performed by the participants. Vascular territories affected by disease were identified using BOLD cerebrovascular reactivity. Preliminary evidence from two patients pre‐ and postrevascularization surgery and four controls indicates that neurovascular coupling in affected brain regions can be modulated by the task‐related vascular demands in unaffected regions. In one patient studied, we observed that brain regions with improved cerebrovascular reactivity after surgery demonstrated normalized neurovascular coupling, that is the degree to which neurovascular coupling was modulated by task‐related vascular demands was decreased. We propose that variations in task‐dependent neurovascular coupling in patients with moyamoya disease are likely related to vascular steal. While preliminary, our findings are a proof of concept of the limitations of BOLD fMRI in cerebrovascular disease and suggest a role for assessment of cerebrovascular reactivity to improve interpretation of task‐related BOLD fMRI activation.